2017
DOI: 10.1016/j.actamat.2017.08.058
|View full text |Cite
|
Sign up to set email alerts
|

Interface-controlled creep in metallic glass composites

Abstract: In this work we present molecular dynamics simulations on the creep behavior of Cu 64 Zr 36 metallic glass composites. Surprisingly, all composites exhibit much higher creep rates than the homogeneous glass. The glass-crystal interface can be viewed as a weak interphase, where the activation of shear transformation zones is lower than in the surrounding glass. We observe that the creep behavior of the composites does not only depend on the interface area but also on the orientation of the interface with respec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 65 publications
(94 reference statements)
1
6
0
Order By: Relevance
“…For obtaining a juvenile homogenous glass, a melt was equilibrated at 2,000 K and then quenched to the glassy state (50 K) using a cooling rate of 0.01 K ps −1 . The atomic structure of the prepared Cu 64 Zr 36 glass shows good agreement with previous studies (Ritter et al, 2011;Cheng et al, 2013;Ding et al, 2014;Zemp et al, 2015;Adjaoud and Albe, 2016;Kalcher et al, 2017b). The Cu 64 Zr 36 nanoglass was obtained by cold compaction of several glassy spheres with diameter ranging from 6 to 8 nm.…”
Section: Methodssupporting
confidence: 86%
“…For obtaining a juvenile homogenous glass, a melt was equilibrated at 2,000 K and then quenched to the glassy state (50 K) using a cooling rate of 0.01 K ps −1 . The atomic structure of the prepared Cu 64 Zr 36 glass shows good agreement with previous studies (Ritter et al, 2011;Cheng et al, 2013;Ding et al, 2014;Zemp et al, 2015;Adjaoud and Albe, 2016;Kalcher et al, 2017b). The Cu 64 Zr 36 nanoglass was obtained by cold compaction of several glassy spheres with diameter ranging from 6 to 8 nm.…”
Section: Methodssupporting
confidence: 86%
“…This is a rather unexpected finding, as typically the introduction of rigid inclusions into a mainly viscous matrix is expected to induce a decrease of the creep rates, that is, particle hardening . Furthermore, it was shown that in the studied compositions the interface orientation has a strong contribution and thus controls the creep behavior of the B2‐CuZr/MG‐Cu 64 Zr 36 nanocomposite …”
Section: Resultsmentioning
confidence: 72%
“…Recently, it was shown in a study related to the creep behavior of nanocomposites consisting of a Cu 64 Zr 36 metallic glass matrix and dispersed B2 CuZr precipitates that an amorphous interface between the dispersed B2 CuZr (nano)particles and the C 64 Zr 36 glass matrix induces a significant increase of the creep rates of the nanocomposite . This is a rather unexpected finding, as typically the introduction of rigid inclusions into a mainly viscous matrix is expected to induce a decrease of the creep rates, that is, particle hardening .…”
Section: Resultsmentioning
confidence: 98%
“…Indeed, this view misses important complexities, such as interactions between contact spots [68], plastic deformations due to the normal load [25,[69][70][71][72], and, as the present paper indicates, slip. This slip depends on the strength of the adhesive bond and the sharpness of the interface, and as such is subject to time-dependent phenomena such as aging [73][74][75] and interface creep [76][77][78][79]. With appropriate knowledge about the parameters of the interface, wear debris formation, surface deformation due to plasticity, and slip can now be treated quantitatively using our framework.…”
Section: Discussionmentioning
confidence: 99%